Development of Anato-Smart Media as an Interactive Learning Media for Elementary School Students Regarding Limb Anatomy - Atik Maftuhah (Journal of Community Empowerment for Health, 2023)
The subject matter of science, especially related to human anatomy, is one of the most challenging to understand. To help understand science materials, especially human body anatomy, we conducted community service by developing the Anato-Smart book as a learning media for students and teachers of 5th grade of Muhammadiyah 1 Elementary School Surakarta in 2021. The method of implementation in this service includes several stages, including determining the topic of the body system for the learning media that would be developed through the Focus Group Discussion for teachers at Muhammadiyah 1 Elementary School Surakarta, followed by the development of interactive and educational story media Anato-Smart with the title “The Adventures of Andi and Si Balung”, then media trials to 5th graders at Muhammadiyah 1 Elementary School Surakarta, as well as interviews and outspread questionnaires for the evaluation of Anato-Smart media. This service activity resulted in an Anato-Smart teaching media developed to hone the students' analytical skills on limb and skeletal topics. Teachers can use this book to augment interactive lessons and as one of the educational resources for students to learn about potential risks and disorders to the limbs and skeleton in daily life. From the evaluation, the story and education concepts in this Anato-Smart media book are intriguing and facilitate comprehension, however, it is better to lessen the words and increase the number of images to make it more interesting for children. We will use this feedback to improve the final results of this media so that it can be used by other schools, not only by Muhammadiyah 1 Elementary School Surakarta. Collaboration with other parties to develop teaching media in the future is needed to produce educational and interactive teaching media.